PENGARUH EPS, CR, DAN KURS TERHADAP RETURN SAHAM SUBSEKTOR FOOD AND BEVERAGE PERIODE 2018– 2022 - Lisa Laelatul Amalia; Renea Shinta Aminda; Immas Nurhayati (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine Earning Per Share (EPS), Current Ratio (CR), and Exchange Rates have an effect both partially and simultaneously on the Stock Return of the Food and Beverage sub-sector listed on the IDX for the period 2018 - 2022. The research sample was 10 companies with 50 observation data in the food and beverage sub-sector listed on the IDX. The analysis method used is quantitative method with test analysis using eviews10 with multiple linear regression panel data with the best model Fixed Effect Model (FEM). Based on the partial test results (t test), it shows that EPS has a significant effect on Stock Returns, the CR variable has no effect on Stock Returns and the Exchange Rate variable has no effect on Stock Returns. The test results simultaneously show that Earning Per Share, Current Ratio, and Exchange Rate have a significant effect on Stock Returns. From this study, profitability information is considered important by companies because this information can be a signal for investors in making transactions and the company's profitability will reflect the company's stock return